People of the river - Gear, W. Michael (Gear, Kathleen O'Neal. First North Americans series., 1992)
This gripping saga tells of the Mound Builders of the Mississippi Valley. In a time of many troubles, a warchief and his people have lost all hope. But hope is revived with a young girl learning to Dream of Power.